Locus amoenus or locus horridus: The Forest of Arden as a setting in "As You Like It" - Wojciechowska, Sylwia (Adam Mickiewicz University, 2010)
As you like it stands out from the rest of Shakespeare’s plays as a comedy of conspicuously unusual dramaturgy. Critics have vindicated its idiosyncratic form claiming that As you like it’s uneventful plot is due to the pastoral character of the play. Along with such typically pastoral elements as song contests or lover’s woes they have listed its setting as an example of an idyllic locus amoenus. This article examines the actual character of the Forest of Arden and turns readers’ attention towards the equivocal image of the place.